C-Reactive protein as a biomarker affecting neurorehabilitation outcomes in post-stroke patients: state of knowledge and global trends in research - Borowicz, Wojciech; Szczepańska, Marta; Rosińczuk, Joanna (Journal of Education, Health and Sport, 2023)
Background: C-reactive protein (CRP) is a commonly determined biomarker of inflammation and may reflect the progression of a vascular disease. CRP values within 12 to 24 hours of stroke symptom onset are an independent predictor of adverse functional outcome in terms of the level of motor recovery in the first year of follow-up. Objective: This study aims to provide a complementary analysis of the scientific literature and critically review studies on the use of CRP as a potential biomarker associated with stroke and affecting the achievement of neurorehabilitation progress in post-stroke patients. Methods: This critical review of the literature was prepared based on the following inclusion criteria: (1) original research, (2) studies indexed in PubMed, Scopus and PEDro databases, (3) full-text articles in English, (4) papers published in 2012 – 2022, and (5) papers addressing the use of PCR assay as a biomarker of rehabilitation effectiveness. Results: Based on a review of PubMed, Scopus and PEDro databases, 47, 56 and 9 papers, respectively, were selected based on precisely selected keywords and included in full for further full text review. In this review, the most important scientific rationale was included in response to the aim of this paper. Summary: Recognition of the role of inflammatory and immunological factors in the development of atherosclerosis and the occurrence of ischaemic stroke provides scope for the search for new methods of stroke risk assessment and the development of new methods to prevent stroke. Further empirical validation and unequivocal demonstration of the levels of CRP as a potential marker that affects the health status of a post-stroke patient are needed to ensure the greatest possible level of motor recovery and ability to function independently in terms of all activities of daily living.